Feasibility of OptiMaL, a Self-Management Programme for Oesophageal Cancer Survivors - Connolly, Deirdre; Algeo, Naomi (My University, 2023)
Introduction: There is limited availability of self-management interventions for oesophageal cancer survivors at present. This study examined the feasibility of OptiMal, a six-week, self-management programme to improve fatigue, mood and health-related quality of life for oesophageal cancer survivors. Methods: A mixed methods design was used to evaluate the feasibility of OptiMal. The quantitative arm of the study examined changes in the Multidimensional Fatigue Inventory, Hospital Anxiety and Depression Scale, and the EQ-5D-3L, administered prior to OptiMal (T1), immediately following completion of OptiMal (T2), and three months following completion (T3). Qualitative inquiry in the study was guided by a qualitative descriptive approach through focus groups investigating the ex- periences of group participants, and individual semi-structured interviews at T3. Qualitative data were analysed using thematic analysis. Results: Two OptiMal programmes were delivered over a six-month period with a total of fourteen individuals who had finished treatment for oesophageal cancer. The attendance rate was 89.3%. Statistically significant reductions were observed in fatigue, difficulty performing usual activities, anxiety and depression at three-month follow-up. Qualitative findings identified acceptability of the content and delivery format of OptiMal. Participants reported applying self-management strategies acquired through OptiMal to increase participation in daily activities and improve their health and well-being. Conclusions: This feasibility study yielded promising results in terms of self-management outcomes for oesophageal cancer survivors following attendance of OptiMal. Larger scale research studies with control groups are warranted to examine the outcomes in a robust manner.
PUBLISHED
Keywords: cancer survival; oesophageal cancer; quality of life; self-management; occupational therapy; Cancer; Cancer Survivorship; Occupational Therapy Cancer Survivorship; Self-Management Cancer Survivorship; Chronic Health Condition; Health; Home and community living; Social participation